Depth Analysis of Greyscale Integral Images Using Continuous Multiview Wavelet Transform - Vladimir Saveljev; Irina Palchikova (International Journal of Optics)
The wavelet analysis of the integral images can be used in extraction of the depth of the photographed/synthesized 3D objects. The result of the analysis, however, depends on the colour/texture of the object and thus can be ambiguous. In this paper, we propose to normalize the image before processing in order to avoid such an ambiguity, and to extract the depth without regard to the colour/texture. The proposed technique is verified in multiple integral/plenoptic images and can be applied to multiview and light-field displays as well.